2016
DOI: 10.4103/1119-3077.179293
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception of plastic surgery among tertiary education students in Enugu, South-East Nigeria

Abstract: The level of awareness is high in the sampled population with associated increase in acceptance of its practice and willing utilization. All public hospitals should be encouraged to employ the services of plastic surgeons. Appropriate branding of specialized hospitals where plastic surgery service is available will advance the practice significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 3 publications
0
10
2
Order By: Relevance
“…This was similar to Isiguzo's study where the internet (15.7%), friends (15.7%), and television (14.8%) were noted to be the main source of their information. 7 Easy access to television and internet devices in our age and era may explain the reason why most of the students get their information from these sources. Most satellite TV packages, films, and media available today have stations devoted to aesthetic plastic surgery [15][16][17][18] and as a result, may act as a source of information for the students.…”
Section: Attitudementioning
confidence: 99%
See 4 more Smart Citations
“…This was similar to Isiguzo's study where the internet (15.7%), friends (15.7%), and television (14.8%) were noted to be the main source of their information. 7 Easy access to television and internet devices in our age and era may explain the reason why most of the students get their information from these sources. Most satellite TV packages, films, and media available today have stations devoted to aesthetic plastic surgery [15][16][17][18] and as a result, may act as a source of information for the students.…”
Section: Attitudementioning
confidence: 99%
“…2 In spite of this J Health Allied Sci NU :2020;10:97-101 diversity, several studies across different continents have shown that it is still poorly understood by many, including primary care physicians and medical students. [2][3][4][5][6][7] From these studies, a dearth in knowledge surrounding plastic surgery and particularly a mixed attitude toward its practice has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations